2017
DOI: 10.1016/s0140-6736(16)32572-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events after first, single, mesh and non-mesh surgical procedures for stress urinary incontinence and pelvic organ prolapse in Scotland, 1997–2016: a population-based cohort study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
104
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 22 publications
6
104
1
1
Order By: Relevance
“…The FDA issued a series of statements concluding that serious complications associated with transvaginal mesh for pelvic organ prolapse (POP) repair and are not un-common nevertheless they emphasized that this does not apply to use of mesh for SUI or abdominal surgery. However, very recently, a Scottish population-based study, demonstrated that mesh surgical procedures for SUI were associated with lower risk of early postoperative complications and subsequent prolapse surgery, as well as similar risks of further incontinence surgery and later complications, as compared with open colposuspension [7]. I n late 2015, various working groups worldwide reported on the use of transvaginal mesh in Scotland, England, and Europe (SCENIHR) in surgi cal t reat ment of SUI and P OP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The FDA issued a series of statements concluding that serious complications associated with transvaginal mesh for pelvic organ prolapse (POP) repair and are not un-common nevertheless they emphasized that this does not apply to use of mesh for SUI or abdominal surgery. However, very recently, a Scottish population-based study, demonstrated that mesh surgical procedures for SUI were associated with lower risk of early postoperative complications and subsequent prolapse surgery, as well as similar risks of further incontinence surgery and later complications, as compared with open colposuspension [7]. I n late 2015, various working groups worldwide reported on the use of transvaginal mesh in Scotland, England, and Europe (SCENIHR) in surgi cal t reat ment of SUI and P OP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Research on stress urinary incontinence (SUI) is usually conducted in high-income countries, with more emphasis on surgical interventions [1]. The current mainstay for surgical treatment of SUI is the minimally invasive procedure using a vaginal mesh sling.…”
mentioning
confidence: 99%
“…In recent years, following reports of mesh complications, international authorities have issued alerts regarding the use of mesh, while the controversy has garnered significant media attention [2][3][4]. Accruing evidence shows that mesh is safe in the case of SUI [1,5]. However, what is missing from the bigger picture is that these results mean very little to low-and middle-income countries, where surgical interventions for SUI are either not commonly available or may not be performed due to sociocultural barriers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 A recent study comparing the risks of mesh midurethral slings and traditional non-mesh SUI procedures demonstrated that early surgical complications are lower after midurethral sling and late complications requiring reoperation are similar. 8 Transvaginal mesh slings should not be used in women with urethral diverticulum, urethrovaginal fistula, urethral injury, or prior transvaginal mesh complication (such as pain or mesh erosion).…”
mentioning
confidence: 99%